2016
DOI: 10.1038/srep35240
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting nanowire single-photon detectors with non-periodic dielectric multilayers

Abstract: We present superconducting nanowire single-photon detectors (SSPDs) on non-periodic dielectric multilayers, which enable us to design a variety of wavelength dependences of optical absorptance by optimizing the dielectric multilayer. By adopting a robust simulation to optimize the dielectric multilayer, we designed three types of SSPDs with target wavelengths of 500 nm, 800 nm, and telecom range respectively. We fabricated SSPDs based on the optimized designs for 500 and 800 nm, and evaluated the system detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This issue can be addressed by using superconducting-nanowire single-photon detectors (SSPDs), whose dark counts are much smaller than those of conventional detectors. While SSPDs are usually designed for the infrared region, we recently reported an SSPD design with high detection efficiencies in the visible region 43 . By using such SSPDs, the properties of room-temperature SPSs, which are easily obscured by the dark counts of detectors, may be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…This issue can be addressed by using superconducting-nanowire single-photon detectors (SSPDs), whose dark counts are much smaller than those of conventional detectors. While SSPDs are usually designed for the infrared region, we recently reported an SSPD design with high detection efficiencies in the visible region 43 . By using such SSPDs, the properties of room-temperature SPSs, which are easily obscured by the dark counts of detectors, may be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the extrinsic DCR could be reduced by using cold optical bending fiber [29]. Furthermore, SSPDs with a dielectric multilayer designed to cut the extrinsic DCR also have been presented [31], [32].…”
Section: Sspd Performance In Practical Systemsmentioning
confidence: 99%
“…Maximization of the optical absorbance at the desired wavelength was achieved by optically designing a dielectric mirror consisting of multilayers of two kinds of dielectric materials, such as SiO 2 and TiO 2 , on the substrate. More recently, a nonperiodic dielectric multilayer structure enabling the flexible spectrum (wavelength dependence) design of the optical absorbance in the SSPD was presented [32]. In shortwavelength applications, such as those in the life sciences, a multimode (MM) fiber with a large core is often used to introduce free-space light efficiently.…”
Section: Sspd Performance In Practical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical cavity design has evolved through various ap-*Corresponding author (email: s-miki@nict.go.jp) proaches aimed at obtaining higher η abs : double-side cavity for back side illumination [6,7], optimized optical cavity for front side illumination [8], and cavity with distribution Bragg reflector (DBR) [9][10][11]. It is to be noted that such interesting approaches also made additional attempts to obtain the flexible wavelength spectrum by employing nonperiodic DBR [12], and to reduce the polarization sensitivity by optimizing the optical cavity design [13].Considerable attention has also been focused on obtaining an η int that is as high as possible. Among various approaches aimed at increasing η int , exploration of the optimal superconducting material is one of the most interesting topic.…”
mentioning
confidence: 99%